Epidemiological and Clinical Characteristics of Patients With Coronavirus Disease-2019 in Shiyan City, China - Liu, Long; Lei, Xu; Xiao, Xiao; Yang, Jing; Li, Jian; Ji, Manshan; Du, Weixing; Tan, Huabing; Zhu, Jianyong; Li, Bei; Jin, Zhixiong; Liu, Weiyong; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
To investigate the early epidemic of COVID-19, a total of 176 confirmed COVID-19 cases in Shiyan city, Hubei province, China were surveyed. Our data indicated that the early confirmed COVID-19 cases in Hubei province outside Wuhan were emerged by migrate rate-dependent, and the second-generation patients were mainly cluster-onset between family members from Wuhan travelers. Epidemiological investigation indicated that 10.7% of the COVID-19 cases were transmitted by asymptomatic SARS-CoV-2 infected individuals. Moreover, among the 176 cases, 53 patients were admitted to the Renmin Hospital of Hubei University of Medicine. The clinical characteristics of the 53 patients were collected and compared based on the nucleotides and pneumonia in laboratory inspection. Clinical data showed that 47.2% (25/53) of COVID-19 patients were co-infected with Mycoplasm pneumonia. Thus, we suggest that it is important to assess the transmissibility of asymptomatic infected individuals for SARS-CoV-2 transmission, and it should pay more attentions to the high incidence of coinfections with M. pneumoniae in the COVID-19 patients.